A Review: Meridianins and Meridianins Derivatives - Linxia Xiao (Molecules, 2022)
Meridianins are a family of indole alkaloids derived from Antarctic tunicates with extensive pharmacological activities. A series of meridianin derivatives had been synthesized by drug researchers. This article reviews the extraction and purification methods, biological activities and pharmacological applications, pharmacokinetic characters and chemical synthesis of meridianins and their derivatives. And prospects on discovering new bioactivities of meridianins and optimizing their structure for the improvement of the ADMET properties are provided.